The Geometry of Space and Its Application to Theory of General Relativity, Derivation of Field Equations - Yaremenko, Nikolay Ivanovich (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In this paper we study the geometry of space and applications of this space to general theory of relativity. In space we obtained analog Ricci - Jacobi identity; the geodesic lines equation have been researched; we introduced analog of Darboux theory in case of space, so it was shown the tensor can be presented as the sum of two tensors symmetrical and antisymmetrical with property We discussed some partial cases gravitational and electromagnetic interaction, and their connection to geometry structure; we considered stronger electromagnetic field in space. We derived the general field equations (electromagnetic and gravitational) from the variation principle.